Mast Cells Are Identified in the Lung Parenchyma of Wild Mice, Which Can Be Recapitulated in Naturalized Laboratory Mice - Yeh, Yu-Wen; Chaudhuri, Arka Sen; Zhou, Ling; Fang, Yu; Boysen, Preben; Xiang, Zou (Frontiers in Immunology, 2021)
Background: It is well documented that laboratory mice bred and maintained in ultra-hygienic specific pathogen-free (SPF) barriers display reduced richness and complexity of microbiota compared with wild mice. The laboratory mice profoundly lack lung parenchymal mast cells. Hence, we aimed to investigate the lung distribution of mast cells in free-living wild mice. Methods: Wild house mice were trapped in South-Eastern Norway and Hemtabad, West Bengal, India. C57BL/6 laboratory mice were bred in a purposefully built, closed environment with bedding material obtained from the natural environment with wild rodent infestation in order to normalize the gut microbiota of these laboratory mice to that of the wild mice, and the offspring were collected for study at eight weeks of age. Results: Mast cells were easily identified at a substantial density in the lung parenchymal tissues of wild mice from both Norway and India, which stands in clear contrast to the rare distribution of lung parenchymal mast cells in the conventional laboratory SPF mice. Consistently, wild mice also expressed higher pulmonary levels of stem cell factor, a critical growth factor for mast cell survival. Higher levels of histamine were recorded in the lung tissues of the wild mice. Interestingly, “naturalized” C57BL/6 laboratory mice which spent their entire life in a semi-natural environment developed lung parenchymal mast cells at an appreciable density. Conclusion: Our observations support that environmental factors, possibly through modulation of microbiota, may impact the tissue distribution of mast cells in mouse lung parenchyma.